Hipopituitarizm’li bir olguda koroner arter baypas cerrahisi: Vaka sunumu - (:unkn) unknown (My University, 2009)
Koroner arter baypas cerrahisi yapılan hastalarda preoperatif hipopituitarizm varlığı hem anestezi hem de cerrahi isleme bağlı komplikasyonların görülme riskini arttırmaktadır. Özellikle adrenokortikal ve tiroid hormanlarının uygun dozlarda perioperatif replasmanı bu hasta grubunda yasamsal önem arz etmektedir. Bu yazıda hipopituitarizm nedeniyle takip edilen bir hastada basarılı bir sekilde gerçeklestirilen koroner arter baypas cerrahisi anlatılmıs ve bu hasta grubunda uygulanması gereken optimal peroperatif tedavi stratejisi tartısılmıstır.

Presence of hypopituitarism in patients undergoing coronary artery bypass grafting increases the risks related to both anesthesia and surgery. Perioperative replacement of adrenocortical and thyroid hormones in appropriate amounts plays a vital role in the management of such patients. In this paper successful coronary artery bypass grafting in a patient with hypopituitarism is presented and the perioperative management strategy in these patients is discussed.
Coronary artery bypass grafting in a patient with hypopituitarism: Report of a case
Keywords: Anestezi; Kalp ve Kalp Damar Sistemi